How Southwest Airlines challenged a global crisis - Cameron, Kim (Henry Stewart Talks, 2017)
The case study describes the way Southwest Airlines challenged the accepted belief, supported by nearly all domestic carriers in the US, that jobs would need to be cut in the precarious times following the 9/11 terrorist attack.